The analysis of active compounds in Flos Chrysanthemi Indici by UHPLC Q exactive HF hybrid Quadrupole-Orbitrap MS and comprehensive quality assessment of its preparation. Issue 4 (28th January 2021) - Dai, Tingting; Sun, Guoxiang
Abstract : Active compounds' analysis between Flos Chrysanthemi Indici (FCI) and its preparation (FCIP), and the comprehensive quality assessment of its preparation as well as the correlation analysis between the antioxidant activity and fingerprint. Abstract : Flos Chrysanthemi Indici (FCI) is a common food and its preparation (FCIP) is generally made to realize the medicinal value of FCI in a more accurate and controllable way. In this paper, an efficient UHPLC Q Exactive HF Hybrid Quadrupole-Orbitrap MS method was exploited to elucidate the difference of chemical components between FCI and FCIP. Multi-fingerprints (HPLC-FP, UV-FP, and DSC-FP) were established with the evaluation results integrated by a weighted mean algorithm using variation coefficient (CVWM), which is more objective and reasonable. Through this method, the quality grades of 25 FCIP samples from four manufacturers were successfully discriminated. Meanwhile, the PLS model for the profile-efficacy relationship between the HPLC-FP and the antioxidant activities was established, as well as the correlation between the antioxidant ability (IC50 ) and the DSC curve (enthalpy values) were preliminary explored. In conclusion, this study provides a novel and holistic analytical strategy for food herbal remedies and its preparation.